Exploring social media technologies for novice EFL school teachers to collaborate and communicate: A case in the Czech Republic - Lu, Jinjin; Han, Feifei; Janík, Tomáš (Frontiers in Psychology, 2022)
With an increasing number of international schools, traditional EFL teaching methods may not satisfy students’ needs. This study aims to investigate perceptions of social media technologies (e.g., Web 2.0) and willingness to adopt such technologies to collaborate and communicate in multicultural classrooms among novice EFL schoolteachers in the Czech Republic. The participants were 100 novice EFL schoolteachers in Prague and the South Moravian regions of the Czech Republic. The study used a mixed research method consisting of a survey (stage 1) and a semi-structured interview (stage 2). The survey examined the participants’ appraisal and concerns of using social media technologies to collaborate and to communicate as well as the level of willingness to use social media technologies. A hierarchical cluster analysis using participants’ responses regarding their attitudes and behavioural tendency towards using Web 2.0 social media technologies in language classrooms identified three clusters of teachers. The teachers who were most likely to adopt social Web 2.0 technologies were those who had the highest ratings on both appraisals and concerns regarding the use of social media in language classrooms. The results from the semi-structured interviews were consistent with those from the survey. Together, the results from the two stages demonstrated that most pre-service teachers favoured using Web 2.0 technology for collaboration and communication among colleagues and stakeholders in a broader community, but they displayed contrasting levels of appraisal of and concerns towards using social media technologies. Participants believed that this might be due to their different levels of ICT proficiency, workload, and working environment. The political and practical implications in K-12 education in the Czech context are also discussed.